2016
DOI: 10.1002/bies.201670913
|View full text |Cite
|
Sign up to set email alerts
|

Arf6 and the 5'phosphatase of synaptojanin 1 regulate autophagy in cone photoreceptors

Abstract: Abnormalities in the ability of cells to properly degrade proteins have been identified in many neurodegenerative diseases. Recent work has implicated synaptojanin 1 (SynJ1) in Alzheimer's disease and Parkinson's disease, although the role of this polyphosphoinositide phosphatase in protein degradation has not been thoroughly described. Here, we dissected in vivo the role of SynJ1 in endolysosomal trafficking in zebrafish cone photoreceptors using a SynJ1‐deficient zebrafish mutant, nrca14. We found that loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 71 publications
4
55
0
Order By: Relevance
“…This indicates that it is not just the cycling of Rab7 but PI‐4,5‐P 2 itself that is necessary to control this process. This is consistent with the study that shows that loss of Synaptojanin 1 (SynJ1) in zebrafish during the photoreceptor development process leads to the accumulation of autophagosomes .…”
Section: Roles Of Phosphoinositides In Autophagysupporting
confidence: 93%
“…This indicates that it is not just the cycling of Rab7 but PI‐4,5‐P 2 itself that is necessary to control this process. This is consistent with the study that shows that loss of Synaptojanin 1 (SynJ1) in zebrafish during the photoreceptor development process leads to the accumulation of autophagosomes .…”
Section: Roles Of Phosphoinositides In Autophagysupporting
confidence: 93%
“…Recent work from our laboratory and the Milosevic laboratory has shown that Endophilin A (EndoA), a protein highly enriched at presynapses, has an unexpected role in autophagy (Murdoch et al, 2016;Soukup et al, 2016). In addition, we also found that the EndoA binding partner Synaptojanin 1 (Synj1), a protein also enriched at synapses, can regulate autophagy (Vanhauwaert et al, 2017), corroborating data from zebrafish (George et al, 2016). Both EndoA and Synj1 have well-established roles in synaptic vesicle endocytosis.…”
Section: Autophagy At the Synapse And Its Effect On Synaptic Functionsupporting
confidence: 86%
“…Several transgene techniques are applicable to zebrafish models, such as tissue-specific genomic manipulation and the CRISPR system for genome editing. Moreover, several transgenic reporter lines have been used to monitor the autophagy process, including Tg (CMV:EGFP-Mapllc3b) [30], Tg (TαCP:YFP-2XFYVE) [96], and Tg (TαCP:mCherry-GFP-map1 lc3b) [88,95,97]. These techniques promote the understanding of the physiological functions of autophagy in zebrafish.…”
Section: Zebrafish Modelmentioning
confidence: 99%